The Effect of Self-Efficacy Guidance on Burnout among Inpatient Nurses - Kuswiandarni Kuswiandarni; Blacius Dedi; Tri Ismu Pujiyanto (GLOBAL HEALTH SCIENCE GROUP, 2025)
Burnout is a form of work exhaustion experienced by nurses, whether physically, emotionally or mentally. The tendency for nurses to experience burnout at work will affect the quality of nursing services. The purpose of this study was to determine the effect of self-efficacy guidance on burnout among nurses at the Panti WilasaCitarum Hospital. The research method used was a quasi-experiment, with all nurses at the Panti WilasaCitarum Hospital as respondents. The sample used cluster sampling, taken from 20 nurses in the Cempaka room as the treatment group and 20 nurses in the Dahlia room as the control group. The research instrument used a self-efficacy guidance module and a burnout syndrome questionnaire with a significant correlation level of 0.01 (2-tailed) and Cronbach's alpha reliability of 0.96. The results of the study stated that the level of burnout syndrome in nurses after self-efficacy guidance was found to have decreased significantly by 35% after the self-efficacy guidance treatment. This shows that there is an influence between burnout syndrome and self-efficacy guidance. This study proved to reduce the levels of emotional exhaustion, physical exhaustion, depersonalisation, and reduced self-achievement with a Sign value of 0.000 less than 0.05.